Design and Quantitative Evaluation of a Keycloak-Based Single Sign-On Architecture for Integrated Institutional Information Systems - Nurhadi Nurhadi; Mustazzihim Suhaidi; Muhammad Athariq (ILKOM Jurnal Ilmiah, 2026)
The increasing integration of digital services in higher education institutions requires a secure and scalable authentication mechanism to ensure consistent access across multiple systems. However, fragmented authentication approaches often result in repeated login processes, inconsistent security policies, and inefficient identity management. This study proposes a modular Single Sign-On (SSO) architecture based on Keycloak, integrated with OAuth 2.0, OpenID Connect, and JSON Web Tokens (JWT), to support unified authentication in institutional information systems. A quantitative experimental approach is employed to evaluate system performance in a real academic environment involving 100 user accounts. The evaluation focuses on authentication efficiency, scalability, reliability, and user productivity. The results show a 62% reduction in average login time, an 85% increase in authentication throughput, and a 100% authentication success rate. Scalability testing indicates stable system performance under concurrent workloads, while token validation overhead remains minimal, ensuring that security enhancements do not degrade system responsiveness. In addition, task completion time decreases by 51%, accompanied by a significant improvement in user productivity. These findings demonstrate that the proposed Keycloak-based SSO architecture provides measurable improvements in performance, scalability, security governance, and usability. The study contributes to software systems engineering by presenting a validated architectural model and a comprehensive quantitative evaluation framework for identity management in higher education environments.